Characterization of different types of spent mushroom substrate (SMS) for african catfish (clarias gariepinus) diet suitability - Nur Aziera Abd Rasib (School of Bioprocess Engineering, 2016)
This research is meant to follow certain and rigid objectives as listed below to determine and classify biochemical composition; crude protein, amino acid, total carbohydrate, lignin and fat; heavy metal and ash content of different types of SMS after several cycle of mushroom cultivation; to evaluate the physical properties of formulated fish feed after formulation using Pearson Square method and compare with commercial ones; to investigate the growth performance in term of weight and size of the Catfish throughout fish experimental; to analyze the digestibility of Catfish throughout the feeding trial.